Seismic Impact on Building Structures: Assessment, Design, and Strengthening (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
As the late Professor Nick Ambraseys famously said, “Earthquakes do not kill people—buildings do”. Damage to buildings is one of the most serious physical impacts of earthquakes. Damaged buildings result not only in economic losses but also in human casualties and injuries, a lack of housing, and lost incomes. The seismic resilience of buildings is dictated by a multitude of factors associated with the buildings themselves and their complex interactions with the characteristics of ground shaking. This Special Issue focuses on the structural impact of earthquakes on buildings. Original research and reviews covering structural modeling, vulnerability assessment, performance assessment, design methodology, vibration control/damping, material characterization for innovative use in earthquake-resistant design, performance-based design, forensic analysis, structural pathology and rehabilitation, and repair/strengthening are incorporated into this Special Issue.